Yeasts of the soil – obscure but precious. Issue 5 (2nd March 2018) - Yurkov, Andrey M.
Abstract: Pioneering studies performed in the nineteenth century demonstrated that yeasts are present in below‐ground sources. Soils were regarded more as a reservoir for yeasts that reside in habitats above it. Later studies showed that yeast communities in soils are taxonomically diverse and different from those above‐ground. Soil yeasts possess extraordinary adaptations that allow them to survive in a wide range of environmental conditions. A few species are promising sources of yeast oils and have been used in agriculture as potential antagonists of soil‐borne plant pathogens or as plant growth promoters. Yeasts have been studied mainly in managed soils such as vineyards, orchards and agricultural fields, and to a lesser extent under forests and grasslands. Our knowledge of soil yeasts is further biased towards temperate and boreal forests, whereas data from Africa, the Americas and Asia are scarce. Although soil yeast communities are often species‐poor in a single sample, they are more diverse on the biotope level. Soil yeasts display pronounced endemism along with a surprisingly high proportion of currently unidentified species. However, like other soil inhabitants, yeasts are threatened by habitat alterations owing to anthropogenic activities such as agriculture, deforestation and urbanization. In view of the rapid decline of many natural habitats, the study of soil yeasts in undisturbed or low‐managed biotopes is extremely valuable. The purpose of this review is to encourage researchers, both biologists and soil scientists, to include soil yeasts in future studies. Abstract : Soils are regarded as an important reservoir for yeasts, although data from Africa, the Americas and Asia are scarce. In view of the rapid decline of many natural habitats, the study of soil yeasts in undisturbed or low‐managed biotopes is extremely valuable. Yeasts interact with plants and animals above and below ground; they contribute to nutrient transformation in soils and improve soil aggregate stability.